Handle drag factor - Kleshnev, V. (BioRow, 2020)
In RBN 2011/01, Handle Drag Factor HDF was introduced as a measure of rowing "heaviness"- a "burden factor" of sorts. Here is further analysis of this indicator to make it more understandable and familiar for rowers and coaches.